TRAINING OF TRAINERS METHOD FOR ELEMENTARY SCHOOL TEACHERS TO IMPROVE DENTAL HEALTH KNOWLEDGE - Yudha Rahina; I Gusti Agung Ayu Chandra Iswari Dewi; I Gusti Ayu Ratih Pramesti; Pudak Elang; Eko Sri Yuni Astuti (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Many school children suffered from dental caries, which causes children to skip school because of toothache. The involvement of teachers in schools is considered important. The teacher is a model for children who can provide motivation for proper dental health behavior. The purpose of this study is to provide training to elementary school teachers, to increase their dental health knowledge, in order to educate their students. Materials and Methods: This is a pre-experimental design study, which provides dental health training to teachers. This activity involved 4 dentists as trainers, who had previously performed calibration. There are 2 schools involved, namely Saraswati 1 Elementary School and Saraswati 2 Elementary School in Denpasar Bali. A total of 31 teachers who signed the informed consent were included as samples. Dental health education materials are in the form of power points, animated educational videos, dental models, fluoridated toothpaste and toothbrush for children. The questionnaires were used as an instrument. The educational theme is "prevent cavities by brushing your teeth morning and night. Visit the dentist before it's too late". Data were analyzed using Wilcoxon signed rank test. \ Results and Discussion: At the beginning of the study, it was found that 25.81% of teachers had the poor knowledge category, and 74.19% were in the middle category. There was no teacher with good knowledge category. However, at the end of the study, 100% of the teachers had good dental health knowledge. There are differences in knowledge of teachers before and after receiving training. Conclusion: Dental and oral health training method for elementary school teachers can improve dental health knowledge, so that teachers are worthy to teach dental health to their students.